ANALISIS SISTEM AKUNTANSI KLAIM JAMINAN KECELAKAAN KERJA (JKK) BAGI APARATUR SIPIL NEGARA PADA PT. DANA TABUNGAN DAN ASURANSI PEGAWAI NEGERI (PERSERO) KANTOR CABANG MANADO - Tasikrede, Chicilia C.; Sondakh, Jullie J.; Suwetja, I Gede (Universitas Sam Ratulangi, 2018)
The successful implementation of the tasks of government and national development depends on the working mechanism of state apparatus employees. State Civil Apparatus (ASN) as an element of state apparatus, state servants and public servants have a very important role in implementing national development. On the basis of these circumstances is required efforts to improve welfare, both in the period of active and in retirement. Work Accident Assurance (JKK) is protection against occupational injuries or illnesses in the form of care, compensation, and disability benefits. The purpose of this study is to know the accounting system of work accident assurance claim. The object of this research is the accounting system of claim work accident assurance at PT.Taspen (Persero) KC Manado. The method used is descriptive qualitative analysis. From the accounting system analysis of work accident assurance claim conducted by the author at PT. Taspen (Persero) KC Manado obtained the result that the accounting system of work accident assurance claim that has been implemented effectively and in accordance with existing procedures, seen with the clear separation of duties between the relevant functions and authorization of the authorized party for transactions of payment claim.Keywords: Accounting System, Work Accident Warranty Claim, ASN